Hybrid stars with sequential phase transitions : The emergence of the g2 mode - Rodríguez, María Camila (2021)
Neutron stars are the densest objects in the Universe, with M ∼ 1.4M☉ and R ∼ 12 km, and the equation of state associated to their internal composition is still unknown. The extreme conditions to which matter is subjected inside neutron stars could lead to a phase transition in their inner cores, giving rise to a hybrid compact object. The observation of 2M☉ binary pulsars (PSR J1614-2230, PSR J0343+0432 and PSR J0740+6620) strongly constraints theoretical models of the equation of state. Moreover, the detection of gravitational waves emitted during the binary neutron star merger, GW170817, and its electromagnetic counterpart, GRB170817A, impose additional constraints on the tidal deformability. In this work, we investigate hybrid stars with sequential phase transitions hadron-quark-quark in their cores.We assume that both phase transitions are sharp and analyse the rapid and slow phase conversion scenarios. For the outer core, we use modern hadronic equations of state. For the inner core we employ the constant speed of sound parametrization for quark matter. We analyze more than 3000 hybrid equations of state, taking into account the recent observational constraints from neutron stars. The effects of hadron-quark-quark phase transitions on the normal oscillation modes f and g, are studied under the Cowling relativistic approximation. Our results show that, in the slow conversion regime, a second quark-quark phase transition gives rise to a new g2 mode. We discuss the observational implications of our results associated to the gravitational waves detection and the possibility of detecting hints of sequential phase transitions and the associated g2 mode.